2021
DOI: 10.1038/s41598-021-82634-1
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory shear stress induces molecular changes and side population enrichment in primary tumor-derived lung cancer cells with higher metastatic potential

Abstract: Cancer is a leading cause of death and disease worldwide. However, while the survival for patients with primary cancers is improving, the ability to prevent metastatic cancer has not. Once patients develop metastases, their prognosis is dismal. A critical step in metastasis is the transit of cancer cells in the circulatory system. In this hostile microenvironment, variations in pressure and flow can change cellular behavior. However, the effects that circulation has on cancer cells and the metastatic process r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 83 publications
(83 reference statements)
0
19
0
Order By: Relevance
“…Despite decreases in proliferation, there was no significant change in the cell cycle ( Figure 3 B). Studies have shown that exposing suspended cancer cells to fluid flow can alter the expression of mesenchymal and CSC markers [ 16 ]. Twenty-four hours post-FSS, the cells were analyzed for CSC markers CD133 and CD44.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite decreases in proliferation, there was no significant change in the cell cycle ( Figure 3 B). Studies have shown that exposing suspended cancer cells to fluid flow can alter the expression of mesenchymal and CSC markers [ 16 ]. Twenty-four hours post-FSS, the cells were analyzed for CSC markers CD133 and CD44.…”
Section: Resultsmentioning
confidence: 99%
“…Using an isogenic cellular model consisting of cell lines derived from different tissues within the same patient could provide mechanistic insight into how cancer cells evolve to evade apoptosis within the circulation. Recent studies have shown that physiological levels of FSS stress can promote a mesenchymal phenotype and enhance CTC survival in the circulation [ 13 , 14 , 15 , 16 ]. For example, one study demonstrated that lung cancer cells exposed to fluid shear stress show side-population enrichment, hallmarks of EMT, and upregulation of cancer stem cell (CSC) marker CD44 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our pressure-induced subcutaneous tumourforming model of mice is different from that of liver cancer in the context of PHTN in cirrhosis. However, previous studies have suggested that it is feasible to implant cancer cells or stem cells loaded with pressure [43] or shear stress [44,45] in vitro into nude mice and observe tumour formation in vivo and detect the expression of related proteins. Based on previous studies, we used 3D cell culture technology to mix cells into biogels to achieve a better simulation of the tumour mechanical microenvironment in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have used trans-well plates to co-culture the cancer and endothelial cells to examine the transmigration, [10] for example the molecular-to-phenotypic features of tumors for mortality and endothelial invasion. [11] However, those systems still lack shear stress modulation built into the process. Endothelized microfluidics and vessel-on-chip [12] have rapidly emerged as comprehensive humanized models that incorporate sophisticated vascular anatomies and spatiotemporally regulated hydrodynamic flow.…”
Section: Introductionmentioning
confidence: 99%